Pelatihan Pengembangan Desain Aktivitas Belajar Matematika Berbasis Permainan Tradisional (Etnomatematika) menggunakan Canva - Alfonsa Maria Abi; Netty Julinda Marlin Gella; Dyen Erni Lakapu (Jurnal SOLMA, 2026)
Background: Most traditional games in Benlutu village incorporate mathematical concepts that align with elementary school learning outcomes; however, in practice, these games have not been integrated into learning, including at Yaswari Benlutu Catholic Elementary School. Therefore, this Community Partnership Empowerment (PKM) activity was carried out to produce ethnomathematics-based LKPD, focusing on traditional games in Benlutu Village, to improve students' conceptual understanding by providing teachers with training and development in LKPD using Canva. Methods: The implementation method of this PKM activity is divided into 5 stages, namely socialization, training, application of technology, assistance, and evaluation. The results of this Community Partnership Empowerment (PKM) show that the solutions offered to address partner problems are achieved according to the target.  Results: The proposed solution is able to maximize teachers' abilities and knowledge in understanding ethnomathematics in traditional games in Benlutu village. They are also able to design learning activities, create student worksheets (LKPD) using Canva, and implement LKPDs containing designed learning activities in the classroom, with a focus on improving students' conceptual understanding by 100%. Conclusions: The results of validation, practicality tests, and mathematical concept understanding abilities are in the satisfactory category and meet the target.